Successful Treatment of Pegaspargase-Induced Acute Hepatotoxicity with Vitamin B Complex and L-Carnitine. Issue 1 (1st January 2016) - Lu, Gary; Karur, Vinit; Herrington, Jon D.; Walker, Mary G.
Abstract : Pegaspargase is a chemotherapy drug used in the treatment of acute lymphoblastic leukemia (ALL). One of the adverse effects of pegaspargase is hepatotoxicity, which can rapidly lead to liver failure and death. We report a patient with ALL who developed pegaspargase-induced severe hepatotoxicity that was rescued by treatment with vitamin B complex and L-carnitine. Our patient had a quicker response than prior reported cases, suggesting this treatment might be a better regimen.